Desenvolvimento de procedimentos analíticos para a avaliação de nanosuspensões de fertilizantes e efeitos sobre a produtividade de culturas agrícolas - Liberato, Clayton Gondim (Universidade Federal de São Carlos, 2016)
This study was carried out in three steps: 1) production and characterization of nanosuspensions; 2) development of analytical methods for elemental analysis of fertilizers and plant tissues and comparison between inductively coupled plasma optical emission spectrometry (ICP OES) and microwave induced plasma optical emission spectrometry (MIP OES); 3) agronomical experiments in which the monoelementar nanosuspensions containing zinc, calcium or manganese and other commercial fertilizers were applied in lettuce, corn and soybeans. The particle sizes for nanosuspensions were about 4, 8 and 10 times lower than commercialized products based on zinc, calcium and manganese, respectively. Analytical procedures developed for fertilizers analysis by direct analysis of the nanosuspensions and applying the official method were statistically equal and equivalent in both equipments, with recoveries interval from 99 to 102%. The results of the plant tissue analysis showed statistical differences for most of the analytes, however analysis of the certified reference material apple leaves, NIST 1515, showed recoveries from 80 to 100 % for both equipments. The agronomical experiments have shown productivity gains of around 15% for the application of manganese and zinc nanosuspensions in soybeans, compared to other products tested; although the increase in productivity has not been noticeable to corn crop. For lettuce crop was observed that commercial applications and Calcium Nano (200 mg plant-1) contributed for obtaining bigger plants and to a large absorption of calcium.
Development of analytical procedures for evaluation of nanosuspensions of fertilizers and effects on produtivity of agricultural crops.
Keywords: Química analítica; Procedimentos analíticos; Nanosuspensões de fertilizantes; MIP OES; Culturas agrícolas; CIENCIAS EXATAS E DA TERRA::QUIMICA